2012
DOI: 10.4103/0971-6580.94516
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in brain tissue following administration of low and high doses of arsenite and L-ascorbate in Wistar strain rats

Abstract: This study aimed at investigating the mechanism by which sodium arsenite induces brain injury and the role of L-ascorbate. Thirty adult (n=5) Wistar rats weighing between 140 and 160 g were used. Group 1 neither received sodium arsenite nor L-ascorbate (control), group 2 was administered low dose of arsenite only, group 3 received high dose of arsenite only, group 4 was administered L-ascorbate only, group 5 was administered low dose of arsenite and L-ascorbate, and group 6 received high dose of arsenite and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As discussed, arsenite is an important health risk factor and its contribution to respiratory illness is significant, with mechanisms largely unknown 45 . The investigated response to arsenite treatment is mainly oxidative stress and its regulation at the protein level 46 , 47 . It has been suggested that cells deficient in eIF2α phosphorylation have a higher accumulation of tRNA fragments derived from initiator-tRNA Met in response to arsenite, which may affect the rates of protein synthesis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…As discussed, arsenite is an important health risk factor and its contribution to respiratory illness is significant, with mechanisms largely unknown 45 . The investigated response to arsenite treatment is mainly oxidative stress and its regulation at the protein level 46 , 47 . It has been suggested that cells deficient in eIF2α phosphorylation have a higher accumulation of tRNA fragments derived from initiator-tRNA Met in response to arsenite, which may affect the rates of protein synthesis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Markers of oxidative stress were determined spectrophotometrically. Ferrous Oxidation-Xylenol Assay with Triphenylphosphine was employed to assess the production of hydrogen peroxide as previously described [ 5 , 32 ], while malondialdehyde (MDA) levels were identified as a product of lipid peroxidation by measuring thiobarbituric acid reactive substances (TBARS) [ 5 , 33 ]. The testicular concentrations of Advanced Glycation Endproducts (AGE), a product of oxidative protein denaturation, was determined by ELISA method using standard kits according to the manufacturer's guideline (Elabscience Biotechnology Co Ltd, USA), while reduced glutathione (GSH) levels were determined by spectrophotometric methods using Ellman's procedure [ 5 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lipid peroxidation concentration determination is by measuring the thiobarbituric acid reactive substances (TBARS) produced during lipid peroxidation as previously documented [30]. This method is dependent on the reaction between 2-thiobarbituric acid (TBA) and malondialdehyde, an end product of lipid peroxidation.…”
Section: Estimation Of Testicular Oxidative Markers Anti-oxidants 8ohdg and Caspasementioning
confidence: 99%